A do-it-yourself (DIY) effort towards green innovation and sustainability impact: A case of D’Bag - Anual, Norazlan; Abdul Karim, Zatul Himmah; Mustakim, Nurul Ain; Sauid, Muna Kameelah; Mohamad Roseli, Nur Hazwani (Journal of Islamic, Social, Economics and Development, 2025)
Recycling benefits both the environment and the economy by converting waste into valuable products, thereby safeguarding ecological health. D’Bag is an innovative tote bag crafted from discarded hardcover files and surplus fabric, showcasing creativity while being both attractive and functional. This initiative stems from the understanding that the accumulation of waste leads to a disposal crisis. This study aimed to explore the fate of broken hardcover files, gauge interest in DIY recycling projects, and raise public awareness about the significance of recycling in fostering a sustainable mindset. The research also introduces the DIY product D’Bag. An online questionnaire was created and distributed, employing convenience sampling to gather data via Google Forms, with 294 respondents participating through their mobile devices. The study focused on a small sample of potential users, including students and lecturers from the Business Technology Management department. Furthermore, this paper outlines the innovative process of transforming broken files and other inexpensive materials into D’Bag. A design-based research framework consisting of four phases was utilized in the development of this DIY innovation. The findings revealed that 42.9% of respondents engage in recycling, while 39% retain their files without any intention to recycle. Upon presenting the innovative DIY product known as D’Bag, 69.7% of participants expressed that they found it highly intriguing, while 86.7% indicated a willingness to undertake a similar DIY project. Clearly, imaginative individuals inspire fresh concepts and foster enjoyable new pastimes. D’Bag serves as a prime example of a DIY initiative designed to demonstrate how items typically regarded as waste can be transformed into something valuable. It is advisable for everyone to dedicate time to engage in DIY activities, particularly with damaged hardcover files found in their homes or offices.